Academic Agendas of Sustainable Fashion and Its Relevance With the SDGs Since the Rana Plaza Collapse (Asian Journal of Social Science Studies, 2024)
The sustainable fashion (SF) movement can enhance the lives of producer communities in both developed and developing countries by addressing socio-environmental impacts. However, despite the growing attention, the concept of SF remains unclear to many people. This study examines the academic agendas of SF since the Rana Plaza collapse and addresses how they align with the United Nations’ Sustainable Development Goals. The study analyzes 2,026 research articles from 2013 to 2023 and identifies 17 topics using automated content analyses. These outline how SF studies have gained academic interest in various fields over the past decade. Additionally, the coding results emphasize economic factors more than social and environmental factors. Although the fashion industry plays a vital role in economic development and offers a competitive export commodity for leveraging an abundant workforce in developing countries, they must improve their competitiveness by adopting alternative strategies rather than competing solely on low labor costs. This study suggests enhancing transparency through sustainable supply chains, contributing to the social aspect of SF. Sustainability is an evolving concept closely linked to social, economic, and ecological systems. Researchers and managers must understand its changing meaning over time and effectively communicate it to society.